The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1139/apnm-2013-0105
|View full text |Cite
|
Sign up to set email alerts
|

Bone resorption is suppressed immediately after the third and fourth days of multiday cycling but persistently increased following overnight recovery

Abstract: Previous studies suggest that seasoned cyclists may incur a low bone mineral density. This study investigated the effect of multiday cycling on bone turnover. Ten male cyclists completed 4 consecutive days of cycling for 3 h·day −1 . Sweat calcium excretion during exercise and serum calcium, cortisol, bone formation marker (bone alkaline phosphotase (bone-ALP)), bone resorptive marker (C-terminal telopeptide of type I collagen (␤-CTX)), and parathyroid hormone concentration were measured before and immediately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Further, unpublished data from our laboratory show that elite triathletes have mean resting bone turnover marker concentrations that are higher than the trained runners and triathletes. This is supported by Oosthuyse et al (25) who showed that bone resorption and bone formation markers were significantly elevated each morning after four successive 3 h cycling bouts in well-trained cyclists. Although this is speculative, elite athletes may experience an imbalance between whole-body rates of resorption and formation or, defective coupling (26), meaning that neither bone resorption or bone formation is performed adequately and the quality of the bone may be poorer.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Further, unpublished data from our laboratory show that elite triathletes have mean resting bone turnover marker concentrations that are higher than the trained runners and triathletes. This is supported by Oosthuyse et al (25) who showed that bone resorption and bone formation markers were significantly elevated each morning after four successive 3 h cycling bouts in well-trained cyclists. Although this is speculative, elite athletes may experience an imbalance between whole-body rates of resorption and formation or, defective coupling (26), meaning that neither bone resorption or bone formation is performed adequately and the quality of the bone may be poorer.…”
Section: Discussionsupporting
confidence: 52%
“…Although this increased bone turnover response may be positive in sub-elite populations, elite athletes that train multiple times a day with minimal recovery time and rest days are more likely to suffer from consistently increased bone remodelling, which may have detrimental effects on bone health and enhance the stress fracture risk (25,26,28,30). The trained runners and triathletes in the present study have mean resting bone turnover marker concentrations that are at the upper end of the reference ranges for the non-active, healthy population (7,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…This bone turnover marker is related to bone resorption, and some studies suggest that it is one of the least influenced by intensive physical exercise bone turnover markers [ 3 , 33 ]. On the contrary, there are studies that show that aerobic exercise bouts increase cTX in male triathletes [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fluid retention (L) = ingested fluid volume -urine volume -sweat loss Sweat loss was calculated according to the equations of Cheuvront et al (2007) as the change in body mass from pre to post exercise plus the volume of fluid ingested minus the volume of urine excreted, and minus respiratory water loss and CO 2 /O 2 exchange measured by indirect calorimetry, as described previously (Oosthuyse et al 2014).…”
Section: Sample Analysis and Fluid Balance Calculationsmentioning
confidence: 99%